Особливості політичної системи Швеції: досвід для України - Моренчук, Андрій Андрійович; Morenchuk, Andrii Anatolievich (My University, 2018)
Досліджено особливості політичної системи сучасної Швеції. Відмічається, що в країні не існує Конституції у вигляді єдиного кодифікованого акту. Основу конституційного ладу визначають чотири документи: Форма правління; Акт про престолонаслідування; Акт про свободу друку; Основний закон про свободу висловлювань. Вказується, що за формою правління Швеція є конституційною монархією. Повноваження монарха дуже обмежені й зводяться до церемоніальних функцій. Країна накопичила унікальний досвід застосування пропорційної виборчої системи. Її особливі механізми дають змогу забезпечити стабільність парламентської коаліції та уряду. За рахунок значних обмежень повноважень монарха типові функції глави держави розподілені між главою уряду та парламентом. Значними повноваженнями наділені органи місцевого самоврядування. Виділено елементи, які доцільно було б застосувати у вітчизняній практиці. The features of the political system of contemporary Sweden are investigated. It is noted that in the country there is no Constitution in the form of a single codified act. The basis of the constitutional order is determined by four documents: Form of government; Act of succession; Act on freedom of the press; The Basic Law on Freedom of Expression. It is indicated Sweden to be a constitutional monarchy in the form of government. The powers of the monarch are very limited and reduced to ceremonial functions. The country has gained a unique experience in applying of proportional electoral system. Its special mechanisms provide an opportunity to ensure the stability of the parliamentary coalition and government. Due to significant restrictions on the powers of the monarch, the typical functions of the head of state are divided between the head of government and parliament. Local self-government bodies are endowed with significant powers. The elements that are expedient to apply in domestic practice are highlighted.
Features of the Political System of Sweden: Experience for Ukraine
Keywords: політична система; обмежена монархія; пропорційна виборча система; тальман; political system; limited monarchy; proportional electoral system; talman